2023
DOI: 10.1186/s13071-023-05673-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oral, topical and extended-release injectable formulations of moxidectin combined with doxycycline in Dirofilaria immitis naturally infected dogs

Abstract: Background Several studies in both experimentally and naturally infected dogs have reported the adulticide effect of a combination of macrocyclic lactones and doxycycline against Dirofilaria immitis, showing that these protocols can be used as an alternative to melarsomine. The present study evaluated the efficacy of oral, topical and extended-release injectable formulations of moxidectin when combined with doxycycline in dogs naturally infected with D. immitis from a shelter located in souther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This finding is not consistent with other studies ( 43 , 44 ), in which the proportion of antigen-positive dogs was higher than that of Knott-positive dogs. However, one study showed the same pattern with dogs resulted positive with the modified Knott test but negative with the antigen test ( 45 ). The disagreement between the modified Knott test and the antigen test in the present study could be due to the low concentration of free antigen available for detection by serological tests.…”
Section: Discussionmentioning
confidence: 83%
“…This finding is not consistent with other studies ( 43 , 44 ), in which the proportion of antigen-positive dogs was higher than that of Knott-positive dogs. However, one study showed the same pattern with dogs resulted positive with the modified Knott test but negative with the antigen test ( 45 ). The disagreement between the modified Knott test and the antigen test in the present study could be due to the low concentration of free antigen available for detection by serological tests.…”
Section: Discussionmentioning
confidence: 83%
“…In total, 122 heartworm isolates from different hosts were analysed from nine endemic countries, in Europe (Portugal, Spain, Italy, Greece, Hungary, Romania, Slovakia and Ukraine) and a single isolate from Bangladesh (Table 1 ) [ 39 42 ]. A single isolate was collected from a dog from Portugal which travelled with its owners and was diagnosed with D. immitis upon its arrival to Poland; therefore, it is safe to assume that the dog was infected in Portugal.…”
Section: Methodsmentioning
confidence: 99%